C-ISOTOPE CHEMOSTRATIGRAPHIC CORRELATION OF THE UPPER RIPHEAN IN THE URALS AND ARCTIC REGION - Raaben M.E. (My University, 2001)
Two secular variation curves of C-isotope composition in the Late Riphean carbonates are discussed. The curve approximating data on the Upper Riphean deposits of Spitsbergen, Greenland, northwestern Canada, and southwestern Africa (Kaufman and Knoll, 1995) is now accepted as the model one for the second half of this stratigraphic interval and as useful for global correlations. The careful analysis of the used chronometric calibration of that curve shows that it is vulnerable in the lower, relatively older part of the curve. Comparison of the model curve with another one recently obtained for the Karatau Group, the Upper Riphean stratotype in southern Urals (Podkovyrov et al., 1998) demonstrate that they are of the in-phase character. They both depict the identical number of large positive and negative peaks despite the lower amplitudes of δ13C variations in the Uralian section that is conditioned, in general, by the lower values of extreme positive points. The in-phase character of two variation curves suggests, along with biostratigraphic, isotopic-geochronological and regional geological data, that the model one well characterizes not only the second half, but also the older part of the Late Riphean time. The available difference in configuration of uppermost parts of the curves under comparison appears to be a consequence of the Upper Riphean stratotype incompleteness, as there is a large pre-Vendian stratigraphic hiatus and another one below the Uk Formation, which was underestimated in previous works.
Keywords: Riphean; C-isotope; Urals; Arctic region; Докембрий::Протерозой::Рифей; Precambrian::Proterozoic::Riphean